1978
DOI: 10.1111/j.1467-1770.1978.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

INTELLIGENCE AND LANGUAGE PROFICIENCY AS SOURCES OF VARIANCE IN SELF‐REPORTED AFFECTIVE VARIABLES1

Abstract: Self‐reported attitude data over the last decade have often been used as predictors of attained second language proficiency and for other purposes. Three possible sources of non‐random but extraneous vairance in self‐reported attitude data are considered: self‐flattery, response set, and the approval motive. It is suggested that some of the variance in verbal intelligence is common to variance in first and second language proficiency, some of which in turn may be common to the kinds of non‐random sources of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…On the other hand, there have also been reports of small to no statistically significant relationships between self-assessment and other various measures of language ability (Anderson, 1982;Blue, 1988;Janssen-van Dieten, 1989;Oller and Perkins, 1978;Wesche, Morrison, Ready, and Pawley, 1990). Further, there is concern about the ability of learners to accurately self-assess with several studies reporting a tendency toward overestimation of abilities, particularly in the case of less proficient learners (Anderson, 1982;Davidson and Henning, 1985;Ferguson, 1978;Janssen-van Dieten, 1989).…”
mentioning
confidence: 89%
“…On the other hand, there have also been reports of small to no statistically significant relationships between self-assessment and other various measures of language ability (Anderson, 1982;Blue, 1988;Janssen-van Dieten, 1989;Oller and Perkins, 1978;Wesche, Morrison, Ready, and Pawley, 1990). Further, there is concern about the ability of learners to accurately self-assess with several studies reporting a tendency toward overestimation of abilities, particularly in the case of less proficient learners (Anderson, 1982;Davidson and Henning, 1985;Ferguson, 1978;Janssen-van Dieten, 1989).…”
mentioning
confidence: 89%
“…Oller, Baca and Vigil (1977) carried out a study on Mexican-Americans in the state of New Mexico and reached the conclusion that the students who were anti- integrative towards the Anglo-American majority but were instrumentally motivated did better on the proficiency test. One year later, Oller and Perkins (1978) conducted a study on a group of Chinese alumni in America and concluded that positive attitudes towards the students" own cultural group lead to proficiency. Their research to some extent supported the dichotomy of integrative/instrumental; however, they believed that these terms needed to be redefined based on personal traits of the community members.…”
Section: Literature Reviewmentioning
confidence: 99%
“…instrumental and integrative motivation, has been criticized by scholars arguing that this classification fails to cover all factors influencing the learning of foreign languages. One of the main criticisms was the view that the "socio-educational model" hardly takes into account the cognitive aspects of learning and the learning process in different situations (Au, 1988;Crookes & Schmidt, 1991;Oller & Perkins, 1980). For this reason, scholars and specialists presented different patterns of language learning motivation.…”
Section: Introductionmentioning
confidence: 99%